SIZE DIVERSITY SHAPING FINANCIAL CONDITION OF RURAL COMMUNES OF SIEDLCE SUBREGION (Polityki Europejskie, Finanse i Marketing)
Financial condition of basic units of territorial government is a complex phenomenon. Some authors associate it with the financial situation of the particular commune. Knowledge of the conditions influencing the situation enables governing bodies of the territorial government to make proper financial decisions. The aim of the article is an attempt to evaluate the diversity of factors shaping financial condition of communes of Siedlce subregion between 2014 and 2016. Essential data was taken from the Local Data Bank. The following features were taken into account while shaping the level of particular variables in Siedlce subregion: the measure of central tendency as well as the measures of dispersion and concentration. The conducted research indicated that communes in the studied region were the most diverse as far as their own revenue was concerned. However, they were the  most homogenous when it came to the cycle of rotation of budgetary appropriations.